Diagnostic value of effluent endotoxin level in gram-negative peritonitis in CAPD patients - (:unkn) unknown (MULTIMED INC, 2001)
Objective:To evaluate the diagnostic usefulness of effluent endotoxin by Limulus amoebocyte lysate (LAL) assay in gram-negative peritonitis patients on continuous ambulatory peritoneal dialysis (CAPD) therapy. Design: Prospective study with patients serving as their own controls. Standard microbiologic work up and endotoxin analysis of effluents (night dwell) were done during the pre- and posttreatment phases. Setting: Specimens from three teaching hospitals were processed and tested at a common center. Patients were left for treatment at their respective centers without intervention. Patients: 32 clinical peritonitis and 40 infection-free CAPD patients were studied. Results: 75% (n = 24) of cultures were positive: 41.6% (n = 10) gram-negative and 58.4% (n = 14) grampositive bacteria. Effluents of pre- and posttreated gram-negative cultures had endotoxin levels of 1.53 +/- 0.169 and 0.214 +/- 0.085 endotoxin units (EU)/mL, respectively (p < 0.0001); pre- and posttreated gram-positive levels of 0.102 +/- 0.06 and 0.122 =/- 0.052 EU/mL, respectively (p > 0.05); pre- and posttreated culture-negative peritonitis levels of 0.110 +/- 0.025 and 0.087 +/- 0.031 EU/mL, respectively (p > 0.05); peritonitis-free effluents contained 0.117 +/- 0.079 EU/mL. The diagnostic specificity and the sensitivity of LAL assay were 100% and 98.2% respectively. Conclusion: Where initial microbiological work-up cannot demonstrate a pathogen, effluent endotoxin determined by quantitative LAL assay is a useful marker for diagnosis and management, within safe time limits, of gram-negative peritonitis in CAPD patients.
Keywords: Limulus amoebocyte lysate; LAL; gram-negative bacteria; endotoxin; peritonitis; AMEBOCYTE LYSATE ASSAY; DIALYSIS PATIENTS; CONTAINING MEDIA